SUPERVISI DI TAMAN KANAK-KANAK DAN RAUDHATUL ATHFAL - NURAINI (Al-SAMBASY: Jurnal Kajian Pendidikan, 2026)
Supervision at every level of education must be carried out, as it helps nursery schools and Raudhatul Athfal institutions to improve the quality of learning, enhance teacher performance, and ensure that administration and teaching methods meet standards. This is not merely monitoring, but guidance aimed at improving teacher competence, fostering learning innovation, and enhancing the quality of early childhood education services. Broadly speaking, it involves the professional development of teachers and educational staff, ensuring standards are met, problem-solving, and targeted performance. The difference lies in the academic supervision of kindergartens, which focuses more on the national curriculum approach, emphasising the development of children’s motor, cognitive, language, and socio-emotional skills. Meanwhile, at Raudhatul Athfal, supervision emphasises the integration of Islamic values, etiquette, memorisation of short surahs, prayers, and daily worship practices into learning activities. Supervision in kindergartens checks administration and lesson planning in accordance with the national curriculum. Raudhatul Athfal checks the alignment of lesson plans with Islamic values. Kindergartens focus more on cognitive, motor, social-emotional and language development using a general thematic approach or specific methods such as Montessori.